LncRNA MEG3 overexpression modulates proliferation without inducing apoptosis in rat cardiomyoblast h9c2 cells: a transcriptomic approach: lncRNA MEG3 regulates cardiomyoblast growth - Xing, Zhi; Abudureyimu, Shajidan; Abulaiti, Palida; Wang, Yu; Li, Hui; Lyu, Maolin; Gao, Ying (Cellular and Molecular Biology, 2025)
Long non-coding RNAs (lncRNAs) have been implicated in various biological processes including cell proliferation and apoptosis. However, the role of lncRNA-MEG3 in rat cardiomyoblast H9C2 cells remains unclear. In this study, H9C2 cells were genetically modified to overexpress lncRNA MEG3. The proliferation of these cells was evaluated using the Cell Counting Kit-8 (CCK-8) assay and direct imaging techniques. Apoptosis was assessed through flow cytometry, employing Annexin V and propidium iodide (PI) staining. Quantitative PCR was utilized to confirm the overexpression of lncRNA MEG3. Further, differential expression and alternative splicing analyses were conducted using comprehensive transcriptome sequencing. The overexpression of lncRNA MEG3 in H9C2 cells led to a significant reduction in cell proliferation, as evidenced by lower absorbance readings in the CCK-8 assay and reduced cell confluency in imaging analyses. However, flow cytometric analysis revealed no substantial differences in apoptosis between the lncRNA MEG3 overexpressing group and the control. Transcriptomic analyses demonstrated significant changes in gene expression and alternative splicing patterns, highlighting the intricate role of lncRNA MEG3 in cellular regulatory mechanisms. In conclusion, lncRNA MEG3 overexpression in rat cardiomyoblast H9C2 cells significantly inhibits cellular proliferation without markedly inducing apoptosis, suggesting a specific regulatory role in cellular growth processes. The transcriptomic alterations observed underscore the potential of lncRNA MEG3 as a key player in the molecular dynamics of cardiomyoblasts.